Perfil comportamental do executivo: um estudo exploratório - Vergilio, Maria Elizabete; Vanalle, Rosangela Maria (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper presents the result of a research on the behavioral profile of the executives who work in the Brazilianlabor market. The instrument used in order to survey the profile was the Personal Profile Analysis (PPA)method. From the identification of the profile, it is possible to allocate profissionals towards positions orfunctions where the same may achieve greater success, thus decreasing possible performance problems and theirconsequent dismissal due to the non-compatibility with the job.This investigation was elaborated based on data surveyed by a consultancy company located in the state of SãoPaulo,Brazil, along with 200 (two hundred) executives, chosen at random by its databank, belonging tocompanies from various market sectors, in different functions and various hierarchical levels.The evaluation criteria for the personal profile followed the theory by the american psychologist WilliamMoulton Marston, PhD, who describes four types of behavior in the human being, that is: Dominance,Influence, Steadiness and Conscientiousness, from the PPA method, owned by Thomas International Inc, USA.It is concluded that one can predetermine, by a certain margin of error (the method predicts up to 10%), theprofile of the executive who is in the labor market, taking into consideration his/her personal abilities.Keywords: Personal profile; Profile of the executive; Personal evaluation.